Pendampingan Pembukuan Keuangan pada Usaha Mikro Laundry A2 di Kota Palembang - Fitria Marisya; Rolia Wahasusmiah; Marsinah Marsinah; Hatidah Hatidah; M Bambang Purwanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service activity was carried out at Laundry A2 Palembang City with the aim of improving the financial literacy of micro business actors through simple financial bookkeeping assistance. Many micro business actors experience difficulties in recording financial transactions systematically, which has an impact on their inability to evaluate the financial condition of the business accurately. Through a participatory approach and direct training at the place of business, this activity focuses on the importance of recording daily income and expenses, as well as the preparation of monthly income statements. The results of the mentoring show that the owners and employees of A2 Laundry are starting to be able to implement a structured daily bookkeeping system. In addition, the increase in understanding of financial management can be seen from the post-test results, which increased by up to 70% compared to the pre-test. A2 Laundry now has a simple income statement that can be used as a basis for business decision-making. The success of this activity shows that a simple bookkeeping model that is tailored to business needs can be implemented effectively by MSME actors. In the future, similar approaches can be replicated in other micro-enterprises to strengthen the financial foundations of local businesses.